Utilization Of Digital Technology On Student Learning Outcomes - Ranti, Lidiya Rima; Widya, Anggi; Sari, Mulia; Panamuan, Fortunata Blandina; Wiyono, Hadi (Jurnal Pendidikan Sosiologi dan Humaniora, 2025)
The rapid development of digital technology has brought significant changes to 21st-century education. This study aims to analyze the utilization of digital technology in the learning process and its impact on students’ learning outcomes. The method used is qualitative with a literature review approach that identifies, evaluates, and synthesizes various previous studies published between 2020 and 2025. Data were obtained from national and international journals indexed in SINTA, DOAJ, and Google Scholar. The findings indicate that the integration of digital technology through the use of Learning Management Systems (LMS), multimedia applications, and interactive media has a positive effect on students’ motivation, engagement, and academic achievement. Teachers’ digital competence, institutional support, and the availability of infrastructure are key factors determining the success of digital technology implementation. However, several challenges remain, such as limited access, digital literacy gaps between teachers and students, and unequal education policies. In the long term, the use of digital technology contributes to the development of learning independence, critical thinking skills, and collaborative abilities that are essential for lifelong learning. Therefore, the use of digital technology must be balanced with strengthened digital literacy, improved infrastructure, and continuous pedagogical innovation.